006 OP: METHODOLOGICAL LIMITATIONS AND ADVANCES IN STUDYING CULTURE AND MENTAL HEALTH: SIGNIFICANCE OF QUALITATIVE APPROACHES. Issue 4 (12th April 2015) - Patel, R
Abstract : Social Epidemiology has had a long standing position in health research and covers distribution and determinants of health-related states in defined populations. The domain investigates patterns and causality, revealing health inequalities which aim to prevent and control health related issues. Understandably this field of research has advanced biological fields in exploring the relevance of social, cultural, environmental and economic factors that also play a fundamental role in ill health which is crucially ignored in biological standpoints. However, the dynamic of current societies is continuously changing and for example some areas in the UK are distinctively culturally diverse. By using my study of exploring reasons behind low reported rates of mental illness within the Gujarati community in Leicester I will argue that Social Epidemiology is limiting as method of studying in particular ethnic groups and mental health. This presentation will firstly, address the current problems with epidemiological studies in this area such as ecological fallacy, cultural stereotypes and validity of official statistics. Secondly, I will argue that qualitative research and sociological approaches are progressive for studying mental health. With reference to interview data I will outline a few current cultural complexities such as religion, language and changing traditions faced by both first and second generation migrants. Finally, I will conclude by proposing to progress mental health provision for ethnic groups there is much to be learnt about the intrinsic relationship culture has on mental health. Both qualitative methods and sociological approaches accommodate this required necessity. Having recognised the significance qualitative research has in health, we are faced with the problem of incorporating this in the universal province of the medical model of health which indeed is tricky and perhaps not one that is welcomed by all.